Financing Entrepreneurship and the Old‐Boy Network. Issue 2 (4th April 2013) - Inci, Eren; Parker, Simon C.
<x xml:space="preserve">Abstract</x> We study entrepreneurs' start‐up financing from banks and local financiers. An informal network, whose membership cannot be observed by outsiders, conveys the good signals it gets about the hidden types of network entrepreneurs to local financiers, which are then reflected in different loan terms. We show that there are winners and losers as a result of the network even among its members. Because all projects have positive net value, it is efficient to finance them even in the absence of a network. Thus, the formation of the network is inefficient as entrepreneurs incur networking costs for purely redistributive gains in the form of better loan terms as network members.